The Oxford handbook of religion and the American news media - Winston, Diane H., 1951- (New York : Oxford University Press, 2012)
"Whether the issue is the rise of religiously inspired terrorism, the importance of faith based NGOs in global relief and development, or campaigning for evangelical voters in the U.S., religion proliferates in our newspapers and magazines, on our radios and televisions, on our computer screens and, increasingly, our mobile devices. Americans who assumed society was becoming more and more secular have been surprised by religions' rising visibility and central role in current events. Yet this is hardly new: the history of American journalism has deep religious roots, and religion has long been part of the news mix. Providing a wide-ranging examination of how religion interacts with the news by applying the insights of history, sociology, and cultural studies to an analysis of media, faith, and the points at which they meet, The Oxford Handbook of Religion and the American News Media is the go-to volume for both secular and religious journalists and journalism educators, scholars in media studies, journalism studies, religious studies, and American studies. Divided into five sections, this handbook explores the historical relationship between religion and journalism in the USA, how religion is covered in different media, how different religions are reported on, the main narratives of religion coverage, and the religious press."--Publisher's website.
Section One: History. Religion and News in Eighteenth-Century America / David Copeland ;The Penny Press and the Birth of Modern Religion Reporting / Judith M. Buddenbaum ; American Journalism and Religion, 1870-1930 / Richard Flory ; Religion News Coverage between 1930 and 1960 / Debra L. Mason ; Religion in the News Since 9/11 / Stewart M. Hoover ; Late Night Comedy as a Source of Religion News / Lynn Schofield Clark and Jill Dierberg. -- Section Two: The Media. Religion in Print Media / Doug Underwood ; Religion News on the Radio / Peter Manseau ; Religion in Commercial Television News / Michele Rosenthal ; Religion News Online / Debra L. Mason. -- Section Three: Religions. American Catholicism and the Mass-Market Newsweekly / Peter Manseau ; Mainline Protestants and News Narratives / J. Terry Todd ; Orthodox Judaism and the News / Nora L. Rubel ; Media Representations of 'Sunbelt' Evangelicalism / Darren Dochuk ; The Legend of the Assassins in News Coverage of Muslims / Karim H. Karim ; News coverage of The Church of Jesus Christ of Latter-day Saints / Jana Reiss ; News Coverage and Popular Press Reports of the Maharishi Mahesh Yogi / Jane Naomi Iwamura ; American Press Coverage of Buddhism from the 1870s to the Present / Nick Street ; Wicca in the News / Sarah M. Pike ; Media Coverage of Scientology in the United States / Carole M. Cusack. -- Section Four: Issues and Beats. Religion and Politics in Print / Mark Silk ; Media Portrayals of the Moral Majority / John P. Bartkowski and Ashraf Alam ; Evolution, Creationism and Objectivity in the Press / Lauri Lebo ; Alternative Medicine in the Press / Steven Barrie-Anthony ; News Coverage of Religion, Sexuality and AIDS / Diane Winston ; Race and Racism in News Coverage of Religion / Marcia Alesan Dawkins ; Football and Christianity in the News / Annie Blazer ; The Celebrification of Religion in the Age of Infotainment / Kathryn Lofton. -- Section Five: International Coverage. Latin American Religion in the News / Magali do Nascimento Cunha ; American Coverage of Immigration, Islam, and Identity in the UK and the Netherlands / Elizabeth Poole ; American Newspaper Coverage of Islam in the Arab World / Philip Seib ; American News Coverage of Chinese Uighurs / Dalia Hashad ; Religion and Reporting in Africa / Anthea Butler. -- Section Six: The Religious Press. The Independent Catholic Press and Vatican II / Denise P. Ferguson ; The Mainline Protestant Press / Mark Hulsether ; The American Jewish Press / Jonathan D. Sarna ; The Evangelical Press / Ken Waters ; The Muslim Press in the United States / Faiza Hirji ; The African American Religious Press / John M. Giggie.
Includes bibliographical references and index.
Keywords: Mass media in religion -- United States; Mass media -- Religious aspects; Mass media -- United States; Religion and the press -- United States; Journalism, Religious -- United States; Digital media -- Religious aspects; Digital media -- United States